Mejora en el gasoducto del PERÚ LNG utilizando herramientas de ingeniería industrial - Saez Loo, Luis Victoriano (2019)
This document details the assessment process of the Project to upgrade the capacity of the filtering unit at the metering station of PERU LNG S.R.L.’s natural gas pipeline using Industrial Engineering tools. The project initiates after a request to provide additional transportation capacity through PERU LNG S.R.L.’s natural gas pipeline was received to supply the local market and it was approved by upper management. Through the utilization of a cause-effect diagram it was identified that the capacity of the existing facilities along the pipeline shall be assessed to identify possible bottle necks that could impact the transportation capacity of the pipeline.